Layered chitosan-collagen hydrogel/aligned PLLA nanofiber construct for flexor tendon regeneration. (20th November 2016) - Deepthi, S.; Nivedhitha Sundaram, M.; Deepti Kadavan, J.; Jayakumar, R.
Highlights: Layered chitosan-collagen hydrogel/aligned PLLA nanofiber construct was developed. The developed construct mimics native tendon architecture. Alginate coating suppresses peritendinous adhesion by reducing protein adsorption. Enhanced tenocytes growth was seen along the fibers and chitosan-collagen hydrogel. The developed tendon construct would be suitable for flexor tendon regeneration. Abstract: The aim of our study was to develop a tendon construct of electrospun aligned poly (l -lactic acid) (PLLA) nanofibers, to mimic the aligned collagen fiber bundles and layering PLLA fibers with chitosan-collagen hydrogel, to mimic the glycosaminoglycans of sheath ECM for tendon regeneration. The hydrogel coated electrospun membrane was rolled and an outer coating of alginate gel was given to prevent peritendinous adhesion. The developed constructs were characterized by SEM, FT-IR and tensile testing. Protein adsorption studies showed lower protein adsorption on coated scaffolds compared to uncoated scaffolds. The samples were proven to be non-toxic to tenocytes. The chitosan-collagen/PLLA uncoated scaffolds and alginate gel coated chitosan-collagen/PLLA scaffolds showed good cell proliferation. The tenocytes showed good attachment and spreading on the scaffolds. This study indicated that the developed chitosan-collagen/PLLA/alginate scaffold would be suitable for flexor tendon regeneration.